Neural correlates of enhancing question asking and initiations in children with autism spectrum disorders: A Randomized Clinical Trial. (4th March 2022) - Mohammadzaheri, Fereshteh; Koegel, Lynn Kern; Soleymani, Zahra; Khosrowabadi, Reza; Bakhshi, Enayatollah
ABSTRACT: Children diagnosed with autism spectrum disorder (ASD) demonstrate challenges in various areas of social communication. The aim of this study was to examine the effect of Pivotal Response Treatment (PRT) targeting question-asking on brain activity in twenty 6–12-year-old autistic boys, using a Randomized Clinical Trial (RCT) design. Verbal children, diagnosed with autism, who lacked question asking in their communication were matched based on age and mean length utterance (MLU) and were randomly placed in either PRT intervention or treatment as usual (TAU) groups. Sessions were individually administered, lasting for 60 minutes 3 days a week for a two-month period. All children were tested before and after intervention to assess behavioral areas (questions, general communicative skills, and MLU) and both groups underwent electroencephalography for 10 minutes in open and closed eye resting-state conditions to assess neural correlates. Data were analyzed using covariance analysis and post-hoc using Mann-Whitney and Wilcoxon methods. Significant behavioral improvements in the PRT group were observed after intervention that correlated with changes in electroencephalography (EEG) oscillations at several brain regions compared to the TAU group. The results of this study support other studies suggesting collateral neural changes following the PRT.